Metabolic Pathways of Tetraidothyronine and Triidothyronine Production by Thyroid Gland: A Review of Articles - Mansourian, A.R. (Pakistan journal of biological sciences, 2011)
Tetraidothyronine (T4) and Triiodothyronine (T3) are the two vital hormones in human metabolism produced by thyroid gland. The major pathways in thyroid hormone biosynthesis begin with iodine metabolism which occurs in three sequential steps: active iodide transport into thyroid followed by iodide oxidation and subsequent iodination of tyrosyl residues of thyroglobulin (Tg) to produce idotyrosines monoidotyrosine (MIT) and diiodothyrosine (DIT) on Tg. Oxidized iodine and tyrosyle residues which are an aromatic amino acids are integral part of T4 and T3. The thyroid iodine deficiency of either dietary, thyroid malfunction, or disorder of hypothalamus and pituitary to produce enough Thyroid Stimulating Hormone (TSH), eventually lead to hypothyroidism with sever side effects. Iodine oxidation is the initial step for thyroid hormone synthesis within thyroid, is mediated by thyroperoxidase enzyme (TPO), which itself is activated by TSH required for production of MIT and DIT. T4 and T3 are subsequently are synthesized on Tg following MIT and DIT coupling reaction. Thyroid hormones eventually produced and released into circulation through Tg pinocytosis from follicular space and subsequent lysozomal function, a process again stimulated by TSH. The production of T4 and T3 are highly regulated externally by a negative feed-back interrelation between serum T4, T3 and TSH and internally by the elevated iodine within thyroid gland. It is believed the extra iodine concentration within thyroid gland control thyroid hormones synthesis by inhibition of the TPO and hydrogen peroxide (H2O2) formation which is also an essential factor of iodine oxidation, via a complex mechanism. In healthy subjects the entire procedures of T4 and T3 synthesis re-start again following a drop in serum T4 and T3 concentration. On conditions of thyroid disorders, which caused by the distruption of either of above mechanisms, thyroid hormone deficiency and related clinical manifestations eventually begin to show themselves.